Treachery in Outer Space - Rockwell, Carey; Ley, Willy, 1906-1969; Glanzman, Louis (Salt Lake City, UT : Project Gutenberg, 2006)
"Treachery in Outer Space" by Carey Rockwell is a science fiction novel written in the mid-20th century. The story follows Tom Corbett and his fellow cadets, Roger Manning and Astro, as they navigate the challenges of Space Academy and embark on thrilling adventures in outer space, focusing on their preparation for an important space race. The opening of the book presents lively interactions between the upperclassmen and the new cadet candidates, showcasing the mixture of intimidation and camaraderie that defines their experiences at the Academy. Tom, Roger, and Astro portray a blend of mentorship and humor as they hazed the fearful Earthworm cadets, hinting at the larger themes of teamwork and friendship that will emerge throughout their adventures. The plot sets in motion with mentions of space travel, training, and hints of impending danger, preparing the reader for a journey filled with excitement, competition, and the unexpected challenges posed by space piracy and sabotage. (This is an automatically generated summary.)
Release date is 2006-07-08
Greg Weeks, Joseph R. Hauser and the Online Distributed Proofreading Team
Keywords: Science fiction; Astronauts -- Juvenile fiction; Interplanetary voyages -- Juvenile fiction; Corbett, Tom (Fictitious character) -- Juvenile fiction; Space ships -- Juvenile fiction